1985
DOI: 10.1111/j.1600-0765.1985.tb00453.x
|View full text |Cite
|
Sign up to set email alerts
|

Disturbances in bone remodeling during the progress of hamster periodontitis

Abstract: This study was undertaken to follow the changes in bone remodeling during the progress of periodontitis in the hamster. The comparison of quantitative and morphological data showed that the disease is associated with an important disturbance of the remodeling process. The development of bone resorption, preceded by the arrest of the physiological bone formation, is associated with an increase in the extent in reversal ( = empty) lacunae. Bone fonnation refilled only a small number of these lacunae, although in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

1988
1988
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 8 publications
0
16
0
Order By: Relevance
“…Notably, this observation suggests the involvement of mechanical forces (may be osteocyte-mediated) in coupling. Makris and Saffar56 reported concomitant increase in reversal surface and decrease in formation surface, thus suggesting uncoupling, during the progress of hamster periodontitis. Parfitt57 reported that in older people, especially those with osteoporosis, a significant proportion of the eroded surface is covered by flat lining cells.…”
Section: Reversal Surfacesmentioning
confidence: 96%
“…Notably, this observation suggests the involvement of mechanical forces (may be osteocyte-mediated) in coupling. Makris and Saffar56 reported concomitant increase in reversal surface and decrease in formation surface, thus suggesting uncoupling, during the progress of hamster periodontitis. Parfitt57 reported that in older people, especially those with osteoporosis, a significant proportion of the eroded surface is covered by flat lining cells.…”
Section: Reversal Surfacesmentioning
confidence: 96%
“…During periodontitis, bone destruction results from an imbalance between bone formation that is inhibited and bone resorption that is increased [ 31 , 32 ]. P. gingivalis infection had a strong impact on bone metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…P. gingivalis factors promote bone resorption [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ]. In this study, bone resorption was evaluated along the socket of the third molar; the resorption provoked by P. gingivalis infection added to the physiological osteoclastic resorption related to the physiological tooth drift [37] .…”
Section: Discussionmentioning
confidence: 99%
“…Bone remodeling is severely disturbed during the cyclic progression of periodontitis and formative repair episodes are responsible for vigorous bone deposition at the level of endosteal surfaces leading to "corticalization" of the exposed endosteum subjacent to the inflamed gingival and granulation tissues. Resorption in sitespecific areas may be a dominant feature at any given time of the disease and repair episodes may occur at the periphery of a site during the active phases and endosteally during the quiescent phases of the inflammatory process (Makris and Saffar, 1985).…”
Section: Discussionmentioning
confidence: 99%